ROS generation and autophagosome accumulation contribute to the DMAMCL-induced inhibition of glioma cell proliferation by regulating the ROS/MAPK signaling pathway and suppressing the Akt/mTOR signaling pathway - Wang, Yanjun (Onco Targets Ther, 2019)
PURPOSE: Chemotherapy after surgery can prolong the survival of patients with gliomas. Dimethylaminomicheliolide (DMAMCL), a novel chemotherapeutic agent, exhibited antitumor properties in acute myeloid leukemia stem cells and showed an increased drug concentration in the brain. This study aims to investigate the specific anticancer activities and mechanisms of DMAMCL in glioma cells. MATERIALS AND METHODS: In this study, the effects of DMAMCL were evaluated and characterized in U87-MG and U251 glioma cells. Cell viability was assessed by Cell Counting Kit-8. Apoptosis, mitochondrial membrane potential, and intracellular reactive oxygen species (ROS) generation were assessed by fluorescence microscopy. Autophagosome formation was observed with transmission electron microscopy, and the autophagy flux was measured by transfecting cells with mRFP-GFP-LC3 adenoviral vectors. Immunofluorescence and Western blot analyses were used to determine the expression of proteins. RESULTS: In the present study, treatment with DMAMCL decreased cell viability and induced apoptosis in U87-MG and U251 glioma cells. Additionally, DMAMCL activated autophagy-mediated cell death as evidenced by the formation of autophagosomes, accumulation of LC3B-II, inhibition of autophagy flux, and increase in cell viability after cotreatment with an autophagy inhibitor. Subsequent experiments showed that the DMAMCL-induced apoptosis and autophagy were possibly mediated by ROS generation and Akt/mTOR signaling pathway inhibition. On the other hand, the ROS scavenger N-acetyl-L-cysteine and the Akt activator insulin-like growth factor-1 attenuated the DMAMCL-induced autophagy and cell death. CONCLUSION: Our findings revealed that DMAMCL induced apoptosis and autophagic cell death by regulating the ROS/mitogen-activated protein kinase signaling pathway and suppressing the Akt/mTOR signaling pathway in human glioma cells. DMAMCL may be a novel effective anticancer agent, which can target gliomas.